2018
DOI: 10.7717/peerj.4815
|View full text |Cite
|
Sign up to set email alerts
|

High correlation between skin color based on CIELAB color space, epidermal melanocyte ratio, and melanocyte melanin content

Abstract: BackgroundTo treat skin color disorders, such as vitiligo or burns, melanocytes are transplanted for tissue regeneration. However, melanocyte distribution in the human body varies with age and location, making it difficult to select the optimal donor skin to achieve a desired color match. Determining the correlations with the desired skin color measurement based on CIELAB color, epidermal melanocyte numbers, and melanin content of individual melanocytes is critical for clinical application.MethodFifteen foresk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…They demonstrated that although baseline TEWL measurements did not vary based on race or skin type, it was evident in skin barrier function studies that darker skin pigmentation had better skin barrier function 39 . In our study we used reflectance spectroscopy as a quantitative technique for measuring skin color because it does not incorporate assumptions about the nature or amount of pigment in the skin 28 , 43 . The L* parameter of the tristimulus colorimetry system depicts lightness, ranging from black (0) to absolute white (100), and is the most sensitive of the trichromatic values to skin color change 43 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that although baseline TEWL measurements did not vary based on race or skin type, it was evident in skin barrier function studies that darker skin pigmentation had better skin barrier function 39 . In our study we used reflectance spectroscopy as a quantitative technique for measuring skin color because it does not incorporate assumptions about the nature or amount of pigment in the skin 28 , 43 . The L* parameter of the tristimulus colorimetry system depicts lightness, ranging from black (0) to absolute white (100), and is the most sensitive of the trichromatic values to skin color change 43 .…”
Section: Resultsmentioning
confidence: 99%
“…In our study we used reflectance spectroscopy as a quantitative technique for measuring skin color because it does not incorporate assumptions about the nature or amount of pigment in the skin 28 , 43 . The L* parameter of the tristimulus colorimetry system depicts lightness, ranging from black (0) to absolute white (100), and is the most sensitive of the trichromatic values to skin color change 43 . Considering the overlapping range of L* values between and within each self-reported ethnic/racial group in our study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15 It is important to take into account that a* represents erythema of both physiologic and pathologic cause, 12 as it correlates with haemoglobin, skin blood flow and vascularization. 8,15,22,[28][29][30] However, the correlation of a* with haemoglobin is almost linear, and independent of the amount of melanin. 10 Furthermore, erythema values can be influenced by various individual-and environmental-related variables such as age, medication, caffeine intake, orthostatic effects, physical activity, regional and seasonal variation, ambient temperature and humidity rate, and lighting inconsistencies.…”
Section: Interobserver Concordancementioning
confidence: 99%
“…The L∗a∗b∗ color parameters are recommended by the Commission International d’Eclairage, with lightness (L∗) ranging from 0 (maximum darkness) to 100 (maximum brightness), while a∗ and b∗ are negative or positive values on the green-red and blue-yellow axes, respectively ( Nozaki and Makita, 1998 ). Huang et al. (2018) reported a strong correlation ( r = −0.847) between the L∗ value and melanin content of the skin, suggesting L∗ as an objective reversed measurement of skin darkness.…”
Section: Introductionmentioning
confidence: 97%